KARAKTER DAN NILAI-NILAI KEPEMIMPINAN PAMONGPRAJA UNTUK SINERGITAS ORGANISASI DAN PELAYANAN PUBLIK DI KOTA MAKASSAR - Akhir Saleh (Jurnal Pallangga Praja (JPP), 2020)
ABSTRACTThe research aims to analyze the character and values of civil service leadership for organizational synergy and public service. method used is qualitative. The data source in this study is the general public, service users, sub-district head and a portion of the village head and one section, namely the Government Section as an element of the Makassar City Secretariat. Likewise with the regional government partners, among others were several leaders of the ORW and other community organization leaders. The main instrument in data collection is the researchers themselves as human instruments with interview and observation techniques. Data analysis proceeded by inductioninterpretation- conceptualization. The results showed that the Camats had taken the initiative to make new breakthroughs taking initiatives that have access to the reach of far-reaching thinking with visionary and innovative insight, able to build cooperation, and create regional conduciveness through coordination and peace making, although on the other hand is still weak in law enforcement. The results of this study also show that leadership in Makassar City has been able to overcome and make decisions when facing very emergency conditions. Keywords: character, leadership value, civil service.